Efficiency of speed hump in reducing speed hump in reducing speed within higher educational institution area - Nur Munirah, Anuar (2018)
Road hump is one of the most commonly used traffic calming devices in Malaysia. The installation of such traffic calming device has created a more live-able environment with improvement on road safety as a result of lower speeds. Road humps has been widely implemented in Malaysia especially in residential area, but the effectiveness of road humps in reducing the speed within higher educational institution area is not well explored. In order to measure the effectiveness road humps within this area, a study must be carried out to evaluate the efficiency of road humps in reducing speed within Universiti Malaysia Pahang, Gambang Campus. This study was carried out at the un-signalized four legged intersection of Federal Road 222 that located in front of UMP main entrance. Radar gun was used to collect the passenger’s car free flow speed with and without the existence of road humps. It was found that the speed reduction after the installation of two sets of three round-top humps with height 50mm-100mm and width 3.7m-4.0m both-ways was calculated as 56.5%. Paired sample T-tests were carried out to compare the average speed reductions before humps were installed and after the humps were installed. Result from t-test analysis shows a statistically significant difference in terms of average speed reductions before and after the round-top humps were installed that prove the efficiency of road humps in reducing speed within higher educational institution area.